The role of emotional intelligence in shaping pre-service teachers’ cultural beliefs - Sotiria Varis; Asko Tolvanen; Myrto Kyriazopoulou; Anu Laine; Katariina Waltzer; Anna Widlund; Lisa E. Kim; Robert Klassen; Riitta-Leena Metsäpelto (PLoS ONE, 2025)
Cultural beliefs and emotions have become recognised aspects of the teaching profession. This study examined the association between emotional intelligence (EI) and cultural beliefs using self-reported survey data collected from pre-service teachers at the beginning of their studies (N = 777). These pre-service teachers entered teacher education in 2021 and were studying in five different Finnish universities that geographically represent four regions in Finland. The results from the confirmatory factor analysis and the multiple linear regression suggested the four dimensions of EI positively predict the latent factors of both multicultural and egalitarian beliefs. The relationships between the constructs exhibited moderate effect sizes, with slightly stronger associations found for multicultural beliefs (β = 0.38) compared to egalitarian ones (β = 0.26). Moreover, the ‘using emotions’ dimension of EI significantly and positively predicted pre-service teachers’ multicultural beliefs; the use of emotions to guide thinking significantly predicted beliefs favouring cultural diversity. The study provides further empirical evidence for the influence of emotions on beliefs, and stresses the need to address topics pertaining to democratic education more explicitly and consistently in pre-service teacher education.